IL-10 and ARG-1 Concentrations in Bone Marrow and Peripheral Blood of Metastatic Neuroblastoma Patients Do Not Associate with Clinical Outcome. (19th April 2015) - Morandi, Fabio; Croce, Michela; Cangemi, Giuliana; Barco, Sebastiano; Rigo, Valentina; Carlini, Barbara; Amoroso, Loredana; Pistoia, Vito; Ferrini, Silvano; Corrias, Maria Valeria
Abstract : The expression of the immunosuppressive molecules IL-10 and arginase 1 ( ARG-1 ), and of FOXP3 and CD163, as markers of regulatory T cells (Treg) and macrophages, respectively, was evaluated in bone marrow (BM) and peripheral blood (PB) samples collected at diagnosis from patients with metastatic neuroblastoma (NB). IL-10 and ARG-1 plasma concentrations were measured and the association of each parameter with patients' outcome was tested. The percentages of immunosuppressive Treg and type-1 regulatory (Tr1) cells were also determined. In both BM and PB samples, IL-10 mRNA expression was higher in metastatic NB patients than in controls. IL-10 plasma concentration was higher in patients with NB regardless of stage. Neither IL-10 expression nor IL-10 plasma concentration significantly associated with patient survival. In PB samples from metastatic NB patients, ARG-1 and CD163 expression was higher than in controls but their expression did not associate with survival. Moreover, ARG-1 plasma concentration was lower than in controls, and no association with patient outcome was found. Finally, in metastatic NB patients, the percentage of circulating Treg was higher than in controls, whereas that of Tr1 cells was lower. In conclusion, although IL-10 concentration and Treg percentage were increased, their contribution to the natural history of metastatic NB appears uncertain.